(3eONd dEOGQI GdCYeGds - (3SGejI(B, (3adjGTjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3GdJYQja hWHjYI Yde GdGOGQI, CgejJgG eejRGJgG, eY YdGbJgG HGdYdhe GdCNQi hChLg GdGNJdGa Hjf GdGOGQI hGOGQI GdCYeGd HGdGVGaI Gdi GdUaGJ hGdeSDhdjGJ hGdegGQGJ, cPdc JWhQ GdacQ GdGOGQj heOGQSg aj GdYUhQ GdeNJdaI; CjVG GdeOQSI GdcdGSjcjI heOQSI GdYdGbGJ GdGfSGfjI EVGaI Gdi eOQSI GdYdhe GdSdhcjI, hGdfXQjGJ GdMOjKI aj GdGOGQI hhXGFagG ef GdJNWjW hGdJfXje hGdJhLjg hGdQbGHI(B.s
(3eQGLY U(B.125-128s
Keywords: (3EOGQI GdCYeGds